Mengelola Pengasuhan Anak Usia Dini Setelah Perceraian: Sebuah Studi Kualitatif tentang Orang Tua Tunggal - Yusra Mutiara Yuza; Mia Rachmawaty (Universitas Darunnajah, 2026)
Parental divorce represents a significant family transition that reshapes caregiving experiences during early childhood. This study explores the lived parenting experiences of single parents raising young children after divorce within an early childhood education context. Using a qualitative phenomenological approach, the research was conducted at PAUD Matahari, South Jakarta. Participants included three single parents with children aged 5–6 years, supported by early childhood teachers as triangulating informants. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed through iterative coding, thematic clustering, and synthesis of experiential meanings. The findings reveal that single parents experience parenting as an adaptive, intentional process centered on maintaining emotional closeness, open communication, and guided independence-building, despite time constraints and dual-role pressures. Parenting practices were enacted flexibly to support children’s emotional security and social adjustment. In addition, collaboration with early childhood education institutions emerged as an important source of continuity and support. These findings underscore that parenting quality and relational processes, supported by educational collaboration, are central to early childhood development regardless of family structure.